formula = (a^ x)^y
= a ^ ( x * y)
:> (a^2)^3 = a^(2 * 3)
=a^ 6
2007-07-03 04:43:49
·
answer #1
·
answered by Tubby 5
·
0⤊
0⤋
a^6. 2 and 3 are integers uses as exponents.
2007-07-03 11:50:07
·
answer #2
·
answered by cidyah 7
·
0⤊
0⤋
a^(2*3) = a^6
2007-07-03 11:42:55
·
answer #3
·
answered by Grant d 4
·
0⤊
0⤋
The answer, as shown by the previous replies, is a^6.
Here's why:
(a^2)^3 means (a^2) to the third power, that is,
(a^2) * (a^2) * (a^2),
and (a^2) is a*a, so
(a^2) * (a^2) * (a^2) = (a*a) * (a*a) * (a*a) = a*a*a*a*a*a = a^6
This reasoning is perfectly general, so you have
(a^n)^m = a^(n*m)
And this is also why a^n^m is usually interpreted as a^(n^m), since (a^n)^m could have been written a^(n*m)
2007-07-03 11:52:05
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
(a^2)^3 to answer this you just multiply 2 times 3 and the answer is a^6
2007-07-03 11:46:34
·
answer #5
·
answered by ashley 3
·
0⤊
0⤋
Quick guide: (a^m)^n = a^m*n
So....
(a^2)^3 = a^2*3
=a^6
Property used: Power of a Power.
2007-07-03 11:48:56
·
answer #6
·
answered by Christina J ~ spygirl 2
·
0⤊
0⤋
You need to know something about exponents...
a^0=1
a^1=a
(a^p)(a^q)=a^(p+q)
(a^p)^q=a^(pq) <=== This one seems to apply here.
(a^2)^3
2007-07-03 11:54:01
·
answer #7
·
answered by gugliamo00 7
·
0⤊
0⤋
it means that you multiply a power by a power to get the power of a since we have two powers. a^6
2007-07-07 10:49:35
·
answer #8
·
answered by petite fille 2
·
0⤊
0⤋
= a² x a² x a²
= a x a x a x a x a x a
= a^6
Rule
(a^m)^n = a^(mn)
(a²)³ = a^6
2007-07-07 02:38:32
·
answer #9
·
answered by Como 7
·
0⤊
0⤋
(a^2)^3
just mutiply 2*3
a^6
2007-07-03 12:48:23
·
answer #10
·
answered by edik 4
·
0⤊
0⤋